1999
DOI: 10.1074/jbc.274.2.881
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Thermostable Serine-type Protease fromAquifex pyrophilus

Abstract: A gene encoding a serine-type protease has been cloned from Aquifex pyrophilus using a sequence tag containing the consensus sequence of proteases as a probe. Sequence analysis of the cloned gene reveals an open reading frame of 619 residues that has three canonical residues (Asp-140, His-184, and Ser-502) that form the catalytic site of serine-type proteases. The size of the mature form (43 kDa) and its localization in the cell wall fraction indicate that both the NH 2 -and COOHterminal sequences of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The percentage of charged amino acids (Asp, Glu, Arg, and Lys) in each GSP protein is over 20%. It has been shown that salt bridges between charged amino acids are a major factor stabilizing protein structure (7). It is likely, therefore, that intermolecular electrostatic interactions contribute to the formation of the active multiprotein enzyme with a relatively high thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of charged amino acids (Asp, Glu, Arg, and Lys) in each GSP protein is over 20%. It has been shown that salt bridges between charged amino acids are a major factor stabilizing protein structure (7). It is likely, therefore, that intermolecular electrostatic interactions contribute to the formation of the active multiprotein enzyme with a relatively high thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indirectly suggests that the disulfide bridges present in the native enzyme are stabilizing (52). An Aquifex pyrophilus serine protease was recently described that contains eight cysteines (none are present in subtilisin BPN') (64). A dithiothreitol treatment reduced its t 1/2 at 85°C from 90 h to less than 2 h. This destabilization by dithiothreitol at high temperature suggests that this enzyme indeed contains disulfide bridges and that they are highly inaccessible.…”
Section: Disulfide Bridgesmentioning
confidence: 98%
“…The presence of disulfide bonds within several archaeal and thermophilic genomes has been postulated, taking into account the results of a recent computational study based on the combination of genomic data with protein structure [13]. Moreover, the increasing number of solved crystallographic structures has highlighted the presence of disulfide bonds in several hyperthermophilic proteins [10][11][12]14]. The results reported here on multiple disulfide bonds in PfMTAP add a new example, to the few present in the literature, of an intracellular hyperthermophilic protein with disulfide bonds and argue strongly that intracellular disulfides could represent a significant mechanism to achieve superior levels of thermostability.…”
Section: Assignment Of Disulfide Bridgesmentioning
confidence: 99%
“…In recent years, growing attention has been paid to the presence of disulfide bonds in intracellular hyperthermophilic proteins where these covalent links may play a key role in protein stabilization in the extreme thermal environment [10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation